EVALUATION OF REASONABILITY OF INTRODUCTION OF THE AIR EMISSIONS AND WASTEWATER RATING BY TOTAL ORGANIC CARBON IN RB - A. S. Panasiugin; O. A. Belyi; V. V. Khodin; D. P. Mikhalap; Z. N. Chipurko (Литьë и металлургия, 2013)
The evaluation of the expediency of the introduction of normalizing in air emissions and waste water by total organic carbon content based on four aspects: peculiarit y of TOC analysis, expressivit y of TOC analysis, the price of instruments and the field of application of TOC analyzers. At the present time using TOC as normalized indicators in water, air, waste and soil in the Republic of Belarus is not appropriate.